Hubungan Partisipasi Masyarakat terhadap Aktivitas Bank Sampah - Elsusi Martha; Choirun Nisa (YCMM, 2021)
One of the big problems experienced by big cities in Indonesia is solid waste. Garbage can be interpreted as a consequence of waste bank activities that have raised public awareness to play an active role in waste management in the waste bank program. The purpose of this study was to determine the relationship between elements of community participation on waste bank activities. This type of research uses analytic research, namely by analyzing the data obtained during the study through a cross sectional approach, the sample in this study is residents of the community who live in the Tanjung Uma village as many as 100 respondents. The sampling technique is using accidental sampling and statistical analysis using the chi square test. The results of the study of 100 respondents were the relationship with 100% of respondents' motivation (p value = 0.000), 100% relationship with communication (p value = 0.000), 100% cooperative relationship (p value = 0.000), 100% mobilization relationship (p value = 0.000) with waste bank activities. It is concluded from the results of the study that there is a relationship between waste bank activities and motivation, there is a relationship between waste bank activities and communication, there is a relationship between waste bank activities and cooperative activities and there is a relationship between waste bank activities and mobilization. So that citizens must participate properly so that waste bank activities can run well.